2021
DOI: 10.1101/2021.07.20.453146
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 Restructures the Host Chromatin Architecture

Abstract: SARS-CoV-2 has made >190-million infections worldwide, thus it is pivotal to understand the viral impacts on host cells. Many viruses can significantly alter host chromatin, but such roles of SARS-CoV-2 are largely unknown. Here, we characterized the three-dimensional (3D) genome architecture and epigenome landscapes in human cells after SARS-CoV-2 infection, revealing remarkable restructuring of host chromatin architecture. High-resolution Hi-C 3.0 uncovered widespread A compartmental weakening and A-B mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 36 publications
5
34
1
Order By: Relevance
“…By leveraging viral RNA and protein interactomes, we found that six anti-viral factors identi ed in this study belong to the cohesin complex, a central organizer of the three-dimensional (3D) genome structure 31 . Consistent with our nding, a recent study showed that SARS-CoV-2 was able to rewire host chromatin organization in human cells to confer immunological gene deregulation 32 . Our nding of the subunits of the cohesin complex as inhibitors of SARS-CoV-2 infection provides the rst functional evidence to directly support the role of 3D chromatin organization in mediating host-virus interactions.…”
Section: Discussionsupporting
confidence: 92%
“…By leveraging viral RNA and protein interactomes, we found that six anti-viral factors identi ed in this study belong to the cohesin complex, a central organizer of the three-dimensional (3D) genome structure 31 . Consistent with our nding, a recent study showed that SARS-CoV-2 was able to rewire host chromatin organization in human cells to confer immunological gene deregulation 32 . Our nding of the subunits of the cohesin complex as inhibitors of SARS-CoV-2 infection provides the rst functional evidence to directly support the role of 3D chromatin organization in mediating host-virus interactions.…”
Section: Discussionsupporting
confidence: 92%
“…Fitting with previous work indicating that ORF8 affects endoplasmic reticulum (ER) stress pathways 32 , this suggests that ORF8 probably has an ARKSAP-independent function that may promote viral particle formation. Taken together, this work presents a link between a specific SARS-CoV-2 protein and the epigenetic disruptions that occur in response to infection and provides a mechanistic explanation for mounting evidence 12,13,45 that epigenetic disruptions contribute to the severity of COVID-19.…”
Section: Sars-cov-2 Effects On Transcriptionmentioning
confidence: 69%
“…Viruses have been demonstrated to hijack and re-wire the 3D chromatin organization of the host cell for subverting its immune defense system and exerting long-term inflammatory and other gene regulatory effects ( Heinz et al, 2018 ; Liu et al, 2020 ). In light of the ongoing COVID-19 pandemic, Wang et al (2021) recently reported that SARS-CoV-2 infected cells showed a significant ablation of cohesin, another architectural protein complex that collaborates with CTCF to mediate DNA looping ( Dekker and Mirny, 2016 ), within TADs, causing a widespread weakening of intra-TAD chromatin interactions. Furthermore, A/B compartmentalization manifested a drastic perturbation in the form of A-to-B switching, resulting in erosion of the euchromatic A compartment that is coupled with a global decrease in the active histone H3K27ac mark.…”
Section: Higher-order Spatial Genome Organizationmentioning
confidence: 99%